Bank rates predictors and economic growth: Nigeria experience - Okolie, Joseph Obi; Ujuju, Lucky Ejieh; Erhijakpor, Andrew E. O.; Adegbite, Yetunde Abie; Onuorah, Anastasia Chi-Chi (Edelweiss Applied Science and Technology, 2025)
The study examined the effect of bank rate predictors on Nigeria’s economic growth from 1982 to 2022. The bank rate predictors considered are: saving rate (SIR), prime lending rate (PLM), maximum lending rate (MLR), treasury bill rate (TBR), and monetary policy rate (MPR), while economic growth was measured by real gross domestic product (RGDP). The data was collected from the Central Bank of Nigeria Bulletin. The sourced data were tested using auto-regressive distributed lag (ARDL) methodology. The study reported that SIR has p-values of 0.6722 and 0.7512 in the short and long term, respectively. SIR has no effect on RGDP in Nigeria in both periods, whereas PLM has p-values of 0.6620 and 0.6841 in both the short and long term. PLM has a minor effect on Nigeria’s RGDP; MLR has p-values of 0.5528 and 0.5681 in both periods, respectively. MLR has no effect on Nigerian RGDP in both periods, whereas TBR has p-values of 0.4480 and 0.6987 in both the short and long runs. TBR has no significant effect on RGDP in Nigeria in both periods, but MPR has p-values of 0.2916 and 0.2024 in both the short and long runs. MPR has a negligible effect on RGDP in Nigeria in the short term. In light of the data, it is clear that the bank rate measures adopted had a minor influence on RGDP in Nigeria. It was discovered that SIR, PLR, MLR, TBR, and MPR have minimal effects on RGDP in both the short and long term in Nigeria. Hence, the government should utilize its monetary policies to influence interest rates in a way that prevents them from acting as a barrier to investment.